Biologic-pharmacological providing of trainings, competitions and renewal of triathletes - Volodymyr Vodlozerov (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to analyze the main means of biologic-pharmacological providing of triathletes during different periods of sports activity. Material & Methods: studying and generalization of special literature on problem of ensuring efficiency of training, competitive and renewal processes in continuous triathlon, analysis of features of application of sports food, medicamentous means and methods of passive renewal in kinds of sport on endurance. Results: features of biologic-pharmacological providing of sportsmen are considered before, during and after thriathlon competitions, and also expediency of application of methods of passive renewal therapy is shown. Conclusions: sports food is balanced by products of the increased biological value, adequate drinking mode and medicamentous providing play the major role by preparation, successful overcoming of the combined distance and the subsequent full renewal with simultaneous use of methods of passive therapy.